Video documental :los lenguajes en la teatralización popular de la crucifixión en Cotacachi. - Mejía López, Gabriel Paúl (2016)
In the city of Cotacachi, Good Friday has become a date that breaks the daily life of society not only by the importance of their Catholic meaning but on this day, 50 years ago, the popular theatrical performance is carried out the various passages of the passion and death of Jesus Christ. This event has been making Héctor Mejía, and has become a family tradition. This cultural event takes place in Cotacachi in Imbabura province, is known and recognized in their midst as the staging with popular character, it aims to Catholic staging that no part of the institutions but by the initiative of a family: the organization, financing, logistics and clothing donated their managers in its infancy and later would be based on friendship and recognition of their neighbors to the memory of Hector Mejia. With this background a documentary video product developed chart. In which the effort of a man is evidenced by using theater as a means of neighborhood unit, performing a dramatization of the crucifixion. Note that this ritual is not an official event of the Church, but something more popular. The participants in the drama are not professional actors. The creator of the procession is a self-taught in the art field, but with social sensitivity for community organizing.